The challenge of screening for asymptomatic rheumatic heart disease in South Africa - Liesl Zühlke (South African Heart Association, 2017)
Acute rheumatic fever and rheumatic heart disease remain common in the population of South Africa. A recent screening study of asymptomatic schoolchildren in Mozambique and Cambodia makes a compelling case for a shift in the approach to screening for rheumatic heart disease from auscultation to portable echocardiography. Rheumatic heart disease meets all the epidemiological criteria for screening in the South African population. The incorporation of echocardiographic screening programmes into the school health system and in antenatal clinics for the pre-symptomatic diagnosis of rheumatic heart disease could result in the reduction of morbidity and mortality through the early and wide application of secondary antibiotic prophylaxis.